Listing eBay masculinity: erotic exchanges and regulation in 'gay' and 'gay interest' underwear and swimwear auctions. - White, Michele (Journal of Gender Studies, 2010)
eBay underwear and swimwear sellers incorporate gay identities and female masculinities into the eBay site. They indicate that the men depicted in listings are gay, suggest listings that are of interest to gay men, and include unconventional bodily presentations. While eBay asserts its role as a selling platform, gay underwear and swimwear listings are often a byproduct of men's interests in self-display and communication with other men. Their sexual representations conflict with eBay's heteronormative focus and the company often regulates them. I reflect on the political influence gay clothing sellers have when imaging their gym-built bodies, soft flesh, uneven physiques, genital bulges, and flaccid penises. The humanities-oriented methods of close visual, textual, and theoretical analysis assist me in considering over 1000 eBay listings and related profiles from the English-language website. I argue that these sellers deserve critical deliberation because they undermine eBay's normalizing discourses and traditional ideas about gender, sexuality, and embodiment.